2019
DOI: 10.1194/jlr.r089730
|View full text |Cite
|
Sign up to set email alerts
|

The interface between phosphatidylinositol transfer protein function and phosphoinositide signaling in higher eukaryotes

Abstract: P 3 ]. Yeasts (Saccharomyces) synthesize all of these except PtdIns(3,4)P 2 and PtdIns(3,4,5)P 3. This cohort of molecules is produced by a series of reversible phosphorylation and dephosphorylation reactions catalyzed by phosphoinositide kinases (PIKs) and phosphatases, respectively, that target the inositol headgroup at positions C3, C4, and C5 (1, 2). These chemically distinct lipids, although small in number, control an impressively large set of intracellular activities. How is such diversification of biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 277 publications
(404 reference statements)
1
59
0
Order By: Relevance
“…To date, no binding domain able to specifically recognize PI has been described. However, a class I PI transport protein (PITP) is responsible for transferring PI from the ER to the plasma membrane and therefore might be considered a PI‐binding protein . For this reason, we aimed at preparing a set of tools, namely, photo‐cross‐linkable PI derivatives that are able to capture proteins binding to the lipid.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…To date, no binding domain able to specifically recognize PI has been described. However, a class I PI transport protein (PITP) is responsible for transferring PI from the ER to the plasma membrane and therefore might be considered a PI‐binding protein . For this reason, we aimed at preparing a set of tools, namely, photo‐cross‐linkable PI derivatives that are able to capture proteins binding to the lipid.…”
Section: Figurementioning
confidence: 99%
“…Interestingly, with increased uncaging times, cells were successively more stained at the plasma membrane, a location significantly different from the location of the intact caged lipid (Figure B). This indicates that between uncaging and photo‐cross‐linking, the lipid was transferred to the plasma membrane as was described for endogenous PI . It seems that the uncaged lipid is accepted by the major PI transfer proteins PITPα and PITPÎČ (see below).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…In this way, the lipid exchange cycle renders PtdIns a superior substrate for the enzyme. Structure-based predictions that PtdIns-binding is conserved across the Sec14 superfamily, while the nature of the priming lipid is diversified, suggests a mechanism where the PITP acts as a metabolic sensor for activating PtdIns4P signaling in response to a metabolic input (Schaaf et al, 2008;Bankaitis et al, 2010;Grabon et al, 2019).As all characterized Sec14-like PITPs are lipid-binding proteins, interrogation of the priming ligand question has focused on lipids as it is widely presumed that lipid exchange/transfer activity is the common feature amongst these proteins. Recent work suggests the ligand menu for Sec14-like proteins might be broader than previously thought, however.Cavity mapping studies identified the yeast Sec14-like protein Sfh5 as exhibiting an electropositive surface and a uniquely basic 'lipid-binding' cavity -thus suggesting Sfh5 might bind a ligand that is not a lipid (Tripathi et al, 2019).…”
mentioning
confidence: 99%